Wanprestasi Yang Dilakukan Oleh Pelaku Usaha Makanan Atas Pesanan Yang Tidak Sesuai Pada Aplikasi Layanan Antar Jasa Elektronik - Mellenia, Fritta Omea; Fitriana, Zuhda Mila (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2025)
The occurrence of defaults presents specific challenges, particularly in the form of discrepancies in online food purchase services. These inconsistencies can arise in E-commerce application transactions between food services and can lead to severe dissatisfaction. These losses can encompass unproductive time, inconvenience, which leads to difficulties, and even legal ramifications. The objective of this research is to ascertain whether the actions taken by food business participants in response to incorrect orders meet the criteria for breach of contract. Additionally, it seeks to identify and comprehend the legal ramifications of defaults committed by food business participants in relation to orders that do not align with E-commerce applications. This study employs normative legal research methodologies. The data gathering was conducted through the methods of content analysis, literature review, and document examination. The data analysis was conducted utilizing descriptive analytical techniques and a qualitative methodology. The research findings indicate that the Food Delivery Service Provider Business Partner's acts have violated the terms of the contract, leading to legal repercussions. Consequently, the consumer is entitled to pursue proper legal measures in this situation.